PSYCHOMETRIC ANALYSIS OF THE EMOTIONAL EXHAUSTION SCALE OF PRIVATE UNIVERSITY STUDENTS - Dominguez Lara, Sergio Alexis (2013)
The aim of this instrumental study was to analyze the psychometric properties of theEmotional Exhaustion Scale (EES) in a sample of 233 private university students of psychologywith ages between of 16 and 44 years old (M = 20.9). The factor analysis reveals that the EESpresents a one-dimensional structure (a factor that explains 43.361% of the total variance) andthere was a significant and positive correlation between anxiety and depression and a significantand negative correlation with Academic Self-Efficacy. Furthermore, regarding reliability, the ordinalalpha is adequate (.853). To conclude, the EAPESA has suitable psychometric properties to continuevalidation studies, which reaffirms its use as an instrument to evaluate emotional exhaustion.